Letargia profesională: esență, origini, tendințe de manifestare și căi de diminuare - ARION, Liuba (BIBLIOPOLIS, 2026)
The article examines the lethargic professional phenomenon, presents the determining factors and suggestions for its improvement on the bases of a complex study: the analysis of the reports about the activity of the school libraries and of a survey.